Madhya Pradesh Higher Education Reform Policy Options - World Bank (World Bank, Washington, DC, 2017)
In October 2010, the Government of Madhya Pradesh hosted, with World Bank technical advice, a Conference on higher education reform in the State. The Governor, the Chief Minister and the Minister of Higher Education all addressed the Conference and about 150 people attended the event. Subsequently, four regional Conclaves were organized, in which a total of more than 400 people participated, representing the leadership, administrators, faculty and students at universities and colleges across the State. This represents an impressive outreach to the sector stakeholders. This report is written on the cusp of the publication of the Government of India s 12th Five Year Plan. The indications are that the Government of India intends to push ahead with some significant reforms in the higher education sector. Of particular significance for this report is the emphasis, for the first time, on the need to support the improvement of State universities and colleges. The objective of this report is to provide policy makers in Madhya Pradesh with a menu of options for improving the equity, governance and financing of the higher education system in the State. Though the primary audience is policy makers, this report could serve as part of the continued dialogue with the higher education sector on the direction for reform.